Pertanggungjawaban Hukum Pidana Terhadap Tindak Kekerasan Dalam Rumah Tangga - Wita Subekti (Journal Legal Dialectics, 2023)
Domestic Violence (KDRT) is a form of violation of Human Rights (HAM) and a crime against human dignity and a form of violation that must be resolved. This has actually been strictly regulated in the Law, namely Law Number 23 of 2004, Article 1 concerning domestic violence. However, there are many misperceptions among the public regarding Domestic Violence (KDRT), which are considered to be only physical violence, in the form of beatings, slapping by husbands against wives. The increasing number of domestic violence, especially among women, makes the meaning of domestic violence narrow. Even though everyone within the scope of the household can become a victim. Therefore, the purpose of this research is to find out how the criminal law is responsible for acts of domestic violence? And how is the protection for victims to fulfill a sense of justice? The research method used is a qualitative method, Literature review (Library Study), namely data collection techniques by examining various sources of books, journals, or news articles. As for the results of the research, it was found that the perpetrators could be subject to punishment in the form of imprisonment or fines based on Law Number 23 of 2004, Article 44 concerning Domestic Violence and the Criminal Code concerning abuse. And victims receive legal protection as a form of justice, and this protection for victims is regulated in the PKDRT Law chapter VI Article 16 to Article 38. In addition, it is also contained in Law Number 13 of 2006 Concerning the Protection of Witnesses and Victims. Keywords: Legal Responsibility, Violence, KDRT